PEMBUATAN COMPANY PROFIL BERBASIS MULTIMEDIA FLASH PD BPR BANK DAERAH KARANGANYAR - Ratna Arica Rina .; Ayu Fiska Nuryna . (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
Abstract: The development of information technology has developed rapidly, with virtually all areas of business applications has used the information system, so as to promote and develop the business properly. Today multimedia is one way to facilitate the conveying of information, since multimedia can produce something more interesting. One of them can be used to manufacture the company profile. Submission of information used by the Regional Bank Karanganyar PD BPR still use a sedeharna, namely distribution of brochures, books and installation company profile banners. So the optimal information dissemination. Using flash-based company profile is expected to be a medium of information and effective promotional tool to the public.Formulation of the problem of this research is how to make a company profile PD BPR Regional Bank Karanganyar using multimedia flash. This study is limited to the manufacture company profile PD BPR Regional Bank Karanganyar using adobe flash. The purpose of this research is to create a company profile PD BPR Regional Bank Karanganyar flash-based multimedia to promote PD BPR Regional Bank Karanganyar to the public.The benefit of this research is that it can be used as media campaigns and information PD BPR Karanganyar Regional Bank. The research methodology used was observation, literature, interviews, analysis, design company profile, Editing and Implementation. The results achieved in this study is a flash-based multimedia company profile PD BPR Karanganyar Regional Bank are expected to be used as a means of promotion and information.Keyword: company profile, multimedia.